Hidden struggles in cancer treatment: A brief taste of loss - Ayodele, Olubukola (Journal of Global Medicine, 2025)
This reflective article examines a brief personal experience of taste loss to illuminate the often-overlooked challenges encountered by individuals undergoing cancer treatment. Employing both personal narrative and patient case studies, this discussion highlights the limitations inherent in toxicity grading systems, underscores discrepancies between clinical perspectives and patient experiences, and emphasises the importance of shared decision-making processes. The piece contends that extended survival is valuable only when accompanied by dignity, enjoyment, and a sense of personal meaning.